FROM MISSIONARY TO RESEARCHER: PROFESSIONAL IDENTIFICATION OF PUBLIC SCHOOL TEACHERS UN-DERLYING AUTOBIOGRAPHIES WITHIN A CONTINUING EDUCATION PROGRAM - Bagnara, Laura; Ticks, Luciane Kirchhof (fólio - Revista de Letras, 2018)
This research focuses on autobiographies produced by teachers in two distinct moments (beginning and end) during a continuous teaching education program developed in a public school of Santa Maria (RS) in order to analyze the identification teachers established with their profession. To analyze the process of identification with the profession, we consider two textual categories: modality and evaluation (FAIRCLOUGH, 2003:159), since these give an indication of the commitment of the participants with their texts. The results indicate that most participants recurrently assume at the beginning of the continuous teaching education, the role of “Missionary Teacher”. At the end of the reflective process, we identified a realignment of the role of “Researcher Teacher”.